Dimerization of mitophagy receptor BNIP3L/NIX is essential for recruitment of autophagic machinery. Issue 5 (4th May 2021) - Marinković, Mija; Šprung, Matilda; Novak, Ivana
ABSTRACT: Mitophagy is a conserved intracellular catabolic process responsible for the selective removal of dysfunctional or superfluous mitochondria to maintain mitochondrial quality and need in cells. Here, we examine the mechanisms of receptor-mediated mitophagy activation, with the focus on BNIP3L/NIX mitophagy receptor, proven to be indispensable for selective removal of mitochondria during the terminal differentiation of reticulocytes. The molecular mechanisms of selecting damaged mitochondria from healthy ones are still very obscure. We investigated BNIP3L dimerization as a potentially novel molecular mechanism underlying BNIP3L-dependent mitophagy. Forming stable homodimers, BNIP3L recruits autophagosomes more robustly than its monomeric form. Amino acid substitutions of key transmembrane residues of BNIP3L, BNIP3L G204A or BNIP3L G208V, led to the abolishment of dimer formation, resulting in the lower LC3A-BNIP3L recognition and subsequently lower mitophagy induction. Moreover, we identified the serine 212 as the main amino acid residue at the C-terminal of BNIP3L, which extends to the intermembrane space, responsible for dimerization. In accordance, the phosphomimetic mutation BNIP3L S212E leads to a complete loss of BNIP3L dimerization. Thus, the interplay between BNIP3L phosphorylation and dimerization indicates that the combined mechanism of LIR phosphorylation and receptor dimerization is needed for proper BNIP3L-dependent mitophagy initiation and progression. Abbreviations: AMBRA1: autophagy and beclin 1 regulator 1; Baf A1: bafilomycin A1 ; BH3: BCL2 homology 3; BNIP3: BCL2 interacting protein 3; BNIP3L/NIX: BCL2 interacting protein 3 like; CCCP: carbonyl cyanide 3-chlorophenylhydrazone; CoCl2 : cobalt (II) chloride; FKBP8: FKBP prolyl isomerase 8; FUNDC1: FUN14 domain containing 1; GABARAP: GABA type A receptor-associated protein; GST: glutathione S-transferase; IMM: inner mitochondrial membrane; LIR: LC3-interacting region; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; OMM: outer mitochondrial membrane; PHB2: prohibitin 2; PI: propidium iodide; PINK1: PTEN induced kinase 1; TM: transmembrane domain; TOMM20: translocase of outer mitochondrial membrane 20